2017
DOI: 10.1016/j.carbon.2017.01.104
|View full text |Cite
|
Sign up to set email alerts
|

Computational insight into the capacitive performance of graphene edge planes

Abstract: Recent experiments have shown that electric double-layer capacitors utilizing electrodes consisting of graphene edge plane exhibit higher capacitance than graphene basal plane electrodes. However, theoretical understanding of this capacitance enhancement is still limited. Here we applied a self-consistent electronic calculation on the electrode/electrolyte interface and found that the capacitance of graphene edge plane depends on the edge type: zigzag edge has higher capacitance than armchair edge. We further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 59 publications
1
57
0
Order By: Relevance
“…With the presence of solid electrode, an evidently multilayer structure of electrolytes was recognized at the interface, principally triggered by the VDW and coulombic interactions. To be specific, the first layer of Na + populations preferred to gather at the valley of neighboring O atoms, while Cl − ions accumulated farther away from the electrified surface where they could maintain a full hydration shell ,. Nevertheless, the density oscillations became vanished about ∼12 Å away from the electrode surface, consistent with previous theoretical studies ,.…”
Section: Resultssupporting
confidence: 87%
“…With the presence of solid electrode, an evidently multilayer structure of electrolytes was recognized at the interface, principally triggered by the VDW and coulombic interactions. To be specific, the first layer of Na + populations preferred to gather at the valley of neighboring O atoms, while Cl − ions accumulated farther away from the electrified surface where they could maintain a full hydration shell ,. Nevertheless, the density oscillations became vanished about ∼12 Å away from the electrode surface, consistent with previous theoretical studies ,.…”
Section: Resultssupporting
confidence: 87%
“…However, since the graphene edges also exhibit typical dielectric behavior, it is necessary to include the dielectric screening contribution in total capacitance with the three‐contribution model . To this end, JDFT was used to study the capacitance of graphene edge planes in contact with an implicit aqueous electrolyte: the electronic chemical potential shift and the electrostatic potential drop across the interface show that armchair and zigzag edges have distinct dielectric screening; the zigzag edge has much higher total capacitance than armchair edge due to its very high C Q ; CMD simulation was also used to study the influence of surface morphology on the C EDL …”
Section: From Graphene To Amorphous Carbonmentioning
confidence: 99%
“…The reduction of capacitive signals could further suggest that the edge functionalities/defects on the graphene sites were reduced with partial restoration of the sp 2 structure. It has been shown that the capacitance of graphene is higher at the edges than the basal planes as the edges provide greater accessibility to the solvent ions and large inhomogeneities of the charges allow greater ion adsorption . It must be noted that the temperature of the EOGN film during the photonic curing process is unknown due to the lack of temperature sensors that operate on microsecond time scales.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the capacitance of graphene is higher at the edges than the basal planes as the edges provide greater accessibility to the solvent ions and large inhomogeneities of the charges allow greater ion adsorption. [71][72][73] It must be noted that the temperature of the EOGN film during the photonic curing process is unknown due to the lack of temperature sensors that operate on microsecond time scales. The thermal treatment in a furnace is limited by the thermal properties of the plastic substrates.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%